Cumplicidade e ações neutras em crimes de lavagem de dinheiro - Lemos, Marcelo Augusto Rodrigues de (2018)
This dissertation handles with the limits between the criminal participation and the known neutral actions. Thus, in the scope of this work, were presented the theoretical review about the following problem: which are the penal conditions to impute, as cumplicity, the agent who incurs in a other person criminal fact through a neutral action in money laundering crimes? The first question is, in this sense, in relation to the conceptualization of the aforementioned neutral actions. In fact, those are the actions that, externally, appear a normality, professionality or innocuity and, by the other hand, internally, are illegal. Therefore, it is an action not manifestly punishable that, inevitably, incurs in other person’s crimes. By examples, we can mention the case of a lawyer who receives his payments from illicit assets or the case of the compliance officer who, by falling to report atypical movements to the inspection institutions, ends up helping in a crime committed by a third party. Thus, the doctrine developed a series of theories concerning this matter. In the presente work, given the adequation, we focus on the points regarding the typicality, either in the objective or subjective scope, so that, in the end, it was drawn, from specific cases, the subsumption of some doctrinal precepts to situations brought by lawyers and compliance officers.